Knowledge, Attitude and Associated Factors Towards Heart Failure Management Among Nurses Working in the Cardiac Unit of Selected Government Hospitals in Addis Ababa, Ethiopia: A Cross-Sectional Study - Demissie BM; Bekele DM; Habte T; Wake AD (Dove Medical Press, 2021)
Betelhem Mesfin Demissie,1 Daniel Mengistu Bekele,2 Teshome Habte,2 Addisu Dabi Wake3 1Nursing Department, College of Health Sciences, Woldiya University, Wollo, Amhara Regional State, Ethiopia; 2School of Nursing and Midwifery, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 3Nursing Department, College of Health Sciences, Arsi University, Asella, Oromia Regional State, EthiopiaCorrespondence: Addisu Dabi WakeNursing Department, College of Health Sciences, Arsi University, P.O. Box: 193/04, Asella, Oromia Regional State, EthiopiaTel +251 910 2867 66Email addansa12@gmail.comBackground: Heart failure (HF) is a global pandemic affecting individuals globally and is rising in magnitude. Despite the advancement of treatment for HF, the problem continues to cause substantial hospitalization, economic costs, disability, morbidity, and mortality. However, knowledge, attitude, and associated factors towards HF management in Ethiopia were unknown.Objective: To assess knowledge, attitude, and associated factors towards HF management of nurses working in the cardiac unit.Methods: An institution-based cross-sectional survey was conducted on 180 nurses working in a cardiac unit at selected government hospitals in Addis Ababa, Ethiopia. The data were collected from March to April 2020 by self-administered questionnaire. The data were analyzed by using SPSS version 24.0 software.Results: A total of 180 nurses were enrolled into the study with a response rate of 95%. The mean age of the participants was 31 years. The majority (105; 58.3%) were females. About 108 (60%) of them were married and 34 (18.9%) of them were qualified with a MSc in nursing. More than two-thirds (134; 74.4%) of them had ≤ 6 years of work experience. The majority (131; 72.8%) of them have not taken training on the management of HF. The level of a good knowledge and positive attitude towards the management of HF were 30.56% (n = 55; 95% CI: 24.20- 37.50) and 94.4% (n = 170; 95% CI: 90.6- 97.8), respectively. Having a monthly income of > 6700 Ethiopian birr (AOR = 3.20, 95% CI: 2.87- 9.58), master's degree in nursing (AOR = 4.35, 95% CI: 3.42- 14.36), having > 6 years of working experience (AOR = 5.21, 95% CI: 4.41- 15.72), and having training about HF management (AOR = 6.18, 95% CI: 4.76, 15.95) were factors significantly associated with knowledge towards HF management.Conclusion: The level of good knowledge towards HF management was very low, while the level of positive attitude towards HF management was satisfactory. Educational programs and comprehensive training are recommended to take place to improve them.Keywords: knowledge, attitude, heart failure management, heart failure, nurse